Service Innovation Dynamic Capabilities Framework: A Case of Water Utilities in South Africa - Shabangu, L.; Letaba, P. (South African Journal of Industrial Engineering, 2025)
South African water utilities’ capability to provide high-quality drinking water service is deteriorating, and the country faces a significant problem with continuous water supply because of rising water demand caused by high population growth, industrialisation, and agricultural activities. A quantitative methodology was used to collect and analyse data. Then a framework for service innovation’s dynamic capabilities was developed to address the deteriorating service capabilities in South African water utilities. The study's contribution is this framework, which integrates ordinary capabilities, managerial dynamic capabilities, service innovation capability, and new and emerging technological concepts to address the water supply problem.